Integrating Sri Aurobindo's Educational Philosophy Into Research Practices: A Transformative Approach For Researchers (International Journal of Food and Nutritional Sciences, 2022)
Today in this era of innovations where discoveries are made each day. As a researcher, one tries to do research work in their fields contributing to the existing knowledge vault in those subject areas. Every researcher built on the previous knowledge which is based on the thoughts of some great man or the other. Researchers are influenced by Sri Aurobindo’s philosophy and to achieve his goals, he gets influenced by his ideals and thoughts and helps in giving direction to his research